Implications of flooding events for the green‐lipped mussels ( Perna canaliculus ): an aquatic health perspective - Joanna S. Copedo; Stephen C. Webb; Norman L. C. Ragg; Andrea C. Alfaro (New Zealand Journal of Marine and Freshwater Research, 2025)
Flood events are increasingly impacting coastal infrastructures and marine organisms. Prominent among these organisms, the green‐lipped mussel, Perna canaliculus , is an important marine ecosystem engineer and one of New Zealand’s key aquaculture species. Although relatively robust, the species may have limited capacity to tolerate acute environmental shocks such as exposure to riverine floodwater. As flood events become more frequent, they may present serendipitous opportunities for further research. Thirty days into a temperature and starvation co‐stressor experiment, a storm event resulted in the staff evacuation and eventual flooding of the research facility. Additional samples for histology were opportunistically collected after the flood waters receded, and the survival of the P. canaliculus was monitored for two weeks post‐event. Although no mortalities were observed post‐flood exposure, histological results indicate that the event did cause the mussels to spawn. Tissue conditions, such as haemocytosis of the gill and digestive gland atrophy, also appeared to be correlated with the flood event; however, the impact on P. canaliculus health was considered negligible. This research highlights not only the importance of targeted research in elucidating the impacts of climate‐related hazards on marine species but the importance of opportunistically incorporating these unforeseen events into the research.